Rhetorical categories and linguistic mechanisms in describing research conditions: a comparative genre-based investigation into researchers' choices in Education and Applied Linguistics - Lim, Jason, Miin-Hwa (2009)
Novice writers of research reports often assume that research methods are generally not mentioned in the Results section of a research paper. The extent to which such an assumption is well-founded can be determined by conducting a mixed-method genre-based study of data obtained from authentic research papers. Using both quantitative and qualitative techniques in a genre analysis of two corpora of Results sections in linguistic and educational research articles, the researcher has investigated the various ways in which research methods are mentioned or reiterated in the Results sections of research reports. The findings have shown that despite the significantly different frequencies of steps related to data collection procedures in the two disciplines, research methods are frequently incorporated in the Results section. What merits attention, however, is an important range of communicative functions and an interesting repertoire of linguistic choices that should be thoroughly studied in the preparation of teaching material aimed at enlightening learners on how research methods need to be described in presenting results. The findings of this study will demonstrate that teaching novice writers how to describe research methods while presenting certain results should in fact constitute an important component in an ESP programme intended to promote academic literacy.